Study on the flow and heat transfer of liquid metal based nanofluid with different nanoparticle radiuses using two-phase lattice Boltzmann method. (March 2016) - Qi, Cong; Liang, Lin; Rao, Zhonghao
Highlights: A two-phase lattice Boltzmann model considering the interaction forces for nanofluid was developed. The nanoparticle distributions and heat transfer characteristics are investigated. A mathematic correlation for Cu–Ga nanofluid is obtained. Abstract: A two-phase lattice Boltzmann model considering the interaction forces of nanofluid has been developed in this paper. It is applied to investigate the flow and natural convection heat transfer of Cu–Ga nanofluid. The effects of different nanoparticle radiuses, interaction forces, aspect ratios of the enclosure, nanoparticle volume fractions, and Rayleigh numbers on the nanoparticle distributions and heat transfer characteristics are investigated. It is found that the nanofluid with small nanoparticle radius significantly improves the heat transfer compared with the nanofluid with big nanoparticle radius. The temperature difference driving force has the biggest effect on the nanoparticle distribution, followed by the Brownian force and drag force, and the other forces have the least effect. The average Nusselt number increases with the increasing aspect ratio of the enclosure, nanoparticle volume fraction and Rayleigh number.